Evaluation of Ecological Potential of Ecotourism Development on Extensive and Focused Outing in Shahreza - Seyed Hojjat Mousavi; Asiyeh Abbasian; Parinaz Zoormand (تحقیقات کاربردی علوم جغرافیایی)
Therefore, this study was to evaluate the ecological potential of Ecotourism development in order to study extensive and focused outing in Shahreza County. In this respect, the ecological model of tourism development assessment was fitted. At first, data of slope, aspect, soil order, bedrock, vegetation, temperature and sunshine hour parameters were obtained, and the appropriate areas maps, from the perspective of each parameter is drawn with due observance of the principles and conditions of the said model, and apply the its thresholds. Then, the final mapping of focused and extensive outing of tourism development was drawn by the integration of prone areas maps. Eventually, the final layer of outing was assessing accuracy through the encounter of the natural attractions and rural centers layers. The results showed that extent about 9.0198 and 3.9526 km2 (0.32% and 0.14%) of the Shahreza County are appropriate for the development of one and two levels of focused outing, respectively. Also, extent about 263.1973 and 298.1843 km2 (9.41% and 10.67%) are appropriate for the development of one and two levels of extensive outing, respectively. The high adaptation of the natural attractions and rural centers to the classes evaluated of ecotourism development maps has been showed the acceptable accuracy of the tourism development and the spatial and land use management maps is the Shahreza County.